La imagen, lo real y lo ficcional: fotografía y narrativa (reflexiones teóricas) - Gustafsson, Jan (Diálogos Latinoamericanos, 2018)
The aim of this article is to study the complex relation between photography and narrative fiction in relation to the use of the former in novels or short stories. As a first hypothesis, I claim that the photographic medium is completely different from other sign-forms or representational vehicles. It is so, due to the consequences of the basic photographic technique: it is, by force, a representation of the “real” and, contrary to most other representations, it “freezes” its object in time. Due to this, the photographic media is directly opposed to narrative fiction, which is, probably, a main reason for the relatively scarce use of photography in narrative literature. However, I suggest that exactly these oppositional features may add a tension to the verbal fiction text and create a metafictional level very attractive for contemporary narrative. These reflections are followed by a discussion of the use of photography in three twenieth-century authors.